2023
DOI: 10.26668/businessreview/2023.v8i2.1506
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Organizational Performance Manufacturing Companies in Indonesia: Feature Extraction

Abstract: Purpose: The purpose of this research is to investigate the effect of knowledge sharing and Organizational Learning on Innovation and Organizational Performance, the innovation role as a mediator of knowledge sharing and Organizational.   Theoretical framework:  Good organizational learning affects organizational performance (Kittikunchotiwut, 2020). Besides, the company need not only source for information from the external environment. Rather, it also needs to search internally to create new idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(52 reference statements)
0
0
0
Order By: Relevance
“…According to Laily and Wahyuni (2017), organizational commitment affects performance, which confirms the hypothesis that organizational commitment influences teacher performance. The study found that higher levels of organizational commitment lead to increased teacher performance.…”
Section: Introductionsupporting
confidence: 67%
“…According to Laily and Wahyuni (2017), organizational commitment affects performance, which confirms the hypothesis that organizational commitment influences teacher performance. The study found that higher levels of organizational commitment lead to increased teacher performance.…”
Section: Introductionsupporting
confidence: 67%
“…AI algorithms can be programmed with inherent biases that may perpetuate discrimination or unfairness against certain groups of candidates. For instance, if an AI algorithm is trained on data that contains biased information, such as past hiring decisions based on gender or ethnicity, the algorithm may replicate these biases in its hiring decisions (Wei & Zhou, 2022;Sari et al, 2023).…”
Section: Ethical Concernsmentioning
confidence: 99%
“…However, measuring the financial activity of the Islamic banks Al-Najjar and Kallaf (2012) is In addition to the well-studied organizational commitment to performance, Wilkins et al (1983) found organizational culture as a critical factor for improving organizational activity in research on organizational and activity culture, which explained the relationship among the two and cultural anthropology. However, Lee and Yu (2004) proposed the concept of organizational culture of pettigrew (1979), which included the concept of cultural anthropology and demonstrated in institutional analysis the relationship among symbols, myths and ritual concepts (Laily et. al 2023).…”
Section: Introductionmentioning
confidence: 99%